Lessons from Hydropower Rich Paraguay - Thanju, Jeewan Prasad; Canese, Ricardo (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
Despite Paraguay being one of the largest net exporters of electricity in the world (for decades and the main electricity exporter in South America accounting for 85% of all exports), it is the second poorest nation in South America after Bolivia. It is the half owner of the 14,000MW Itaipu hydro electric complex. Paraguay gets a small fraction of the market price for the exported electricity to Brazil. The Brazilians viewpoint is that the spirit of the treaty is to recover the investment cost and not the commercial price. Hence, there is widespread discontent among the Paraguayans. One Paraguayan minister has commented that it is a real politik of an ant staring at an elephant. Likewise, in Yacyretá, a 3,100MW hydroelectric plant constructed in association with Argentina, Paraguay is not getting a good return. Construction work was stopped for several years by Argentina due to various reasons. Further, planning and feasibility studies were not done in sufficient detail. It is claimed that environmental and ecological considerations were not undertaken in its planning. Paraguay has not sufficiently benefited from the two huge bi-national hydro power projects. Experience of Paraguay may be good lessons for small but hydropower rich countries such as Nepal. Nepalese Officials dreaming to earn several tens of billions Rupees as export revenue from the half the electricity to be owned by Nepal from the proposed Pancheshwar Dam (6,480MW) need to remember the case of Paraguay. DOI: http://dx.doi.org/10.3126/hn.v9i0.7062 Hydro Nepal Vol.9 July 2011 7-11